ANALYSIS OF CHINA’S ACHIEVEMENTS AS A “LOCOMOTIVE” OF GLOBAL ECONOMIC GROWTH - Макогін, Зоряна; Атаманчук, Заріна; Науменко, Валерія (SWorldJournal, 2022)
China’s important role in global economic development cannot be denied. Ten years ago, China has begun economic globalization by buying foreign companies in North America and Europe. That’s why it is important to determine the factors of China’s success o